DEVELOPMENT OF E-MODULES BASED PjBL USING THE FLIPBOOK APPLICATION FOR CLASS XI STUDENTS OF SMA MATERIALS STATIC FLUID - Linda Ewi Diana; Tuti Hardianti; Rachmat Rizaldi; Sheila Fitriana; Nana Mardiana; Syahwin Syahwin (PROGRES PENDIDIKAN, 2022)
This Study aims to produce the product in the form of the teaching materials in the form of Project Based Learning (PjBL) based E-Modules using the Flibook application on the cognitve learning outcomes of tThis Study aims to produce the product in the form of the teaching materials in the form of Project Based Learning (PjBL) based E-Modules using the Flibook application on the cognitve learning outcomes of the students in grade XI at SMA Negeri 1 Tanjung Morawa. This Research and Development (R&D) method. The development model used is a 4-D model (Define, Design, Development, and Disseminate). The data analysis technique used is the validity and the effectiveness. Based on the results of the research that has been done, it can be concluded that the E-Module is included in the valid and effective criteria. This is shown from the results of the expert validation that giving an aevrage percentage of 3,67% in the valid and good category and the results of students’ daily test scores obtained by an average percentage of 88% in the effective and very good category. Therefore, the Project Based Learning (PjBL) based E-Module is proper to be used as the teaching materials at school.he students in grade XI at SMA Negeri 1 Tanjung Morawa. This Research and Development (R&D) method. The development model used is a 4-D model (Define, Design, Development, and Disseminate). The data analysis technique used is the validity and the effectiveness. Based on the results of the research that has been done, it can be concluded that the E-Module is included in the valid and effective criteria. This is shown from the results of the expert validation that giving an aevrage percentage of 3,67% in the valid and good category and the results of students’ daily test scores obtained by an average percentage of 88% in the effective and very good category. Therefore, the Project Based Learning (PjBL) based E-Module is proper to be used as the teaching materials at school.